Pengaruh Manajemen Sumber Daya Manusia dan Kepuasan Kerja Terhadap Kinerja Karyawan UMKM di Kota Padang - Dedi Wandi; Faradilla Suretno; Nesi Afriani Helsya; Sri Wahyuni Lubis; Yefrinal Andra (Suria Academic Press, 2026)
This study aims to examine the influence of Human Resource Management and Job Satisfaction on Employee Performance in MSMEs. The study employed a quantitative approach. The sample consisted of 120 MSME employees, selected using a simple random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 22. The results indicate that Human Resource Management and Job Satisfaction have a positive and significant influence on Employee Performance, both partially and simultaneously.